Perception and knowledge regarding under-nutrition in children among anganwadi workers: a qualitative study in Berhampur of Ganjam district, Odisha - Kar, Monali; Das, Sangeeta; Sahoo, Sanjaya; Patro, Sithun K.; Palai, Shrabani; Mishra, Biswakaiyan; Satapathy, Durga M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Anganwadi centres (AWCs) remain hub for promoting nutrition in children. For an effective functioning of programs, Anganwadi workers (AWWs) need to have a sound knowledge and perception regarding under-nutrition. A qualitative study (Focus Group Discussion) was conducted with aim to assess perceptions and knowledge of AWWs regarding under-nutrition in 6 domains like about term under-nutrition in children, its causes, identification of it, its community management, advices to be given to parents and knowledge of program related to under-nutrition in their locality. Methods: 2 Focus group discussions (each consisted of 12 members and took around 40-45 minutes) were conducted in December 2018 among AWWs of Berhampur through purposive sampling. One author played role of facilitator who carried out discussions, another acted as recorder who took notes and sociograms were recorded by another author. Audio-visual recordings were done. Data were analysed and a report was created based on grounded theory. Results: Participants had fair knowledge of term under-nutrition. They had good knowledge of causes of under-nutrition in children and knew how to identify. But none of them had proper knowledge of community management of malnutrition (CMAM) in children. Though most of them have knowledge of screening of malnourished children and referral to Nutritional rehabilitation centre, they were unaware of other key components of CMAM. Many AWWs didn’t know much about programs for combating malnutrition; however they were well acquainted with ICDS and VHND. Conclusions: Quality training programs and more sensitisation should be done for Anganwadi workers. Specific training on CMAM should be carried out for them.